Fatigue failure of welded connections at orthotropic bridges - D. Abruzzese; Z.H. Qian (Fracture and Structural Integrity)
Orthotropic decks were applied to the long span bridges after World War II due to several advantages, such as light weight, high strength, few deck joints, durability, rapid construction, life-cycle economy. The fatigue problem of orthotropic decks was realized twenty years ago since fatigue failure was found. In the past two decades large amount of studies and investigations were carried out and fruitful achievements were obtained. It was found that most of the fatigue cracks were occurred at the welded connection details, such as rib-to-deck plate, rib-to-diaphragm, and rib-to-diaphragm-to-deck plate (RDDP). These connections are sensitive to fatigue cracking due to high concentrated stress and residual stress at welded connections. In this paper practical fatigue failure cases at the welded connections, ease to occur fatigue cracking, are presented, and analyzed through a numerical modeling of orthotropic deck via FE (finite element) software. Furthermore, the improvement technologies of fatigue are also discussed. The results of the analysis can be contributed to the evaluation of the fatigue design for the orthotropic deck.